DOI: 10.1007/978-1-4020-6438-8_3
|View full text |Cite
|
Sign up to set email alerts
|

Issues and Challenges of Incorporating Fuzzy Sets in Ecological Modeling

Abstract: Abstract. An information-based framework is presented for spatially explicit GIS-based ecological modeling. Within this framework some of the important issues and challenges of incorporating fuzzy sets in spatially explicit population models (SEPM) are discussed. Examples of current work are used to illustrate the main issues and challenges facing the incorporation of fuzzy sets in ecological modeling. Among the challenges to be discussed are fuzzy-based techniques for data acquisition, model control/ evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…This study found that discrete classification schemes were the dominant models used to represent land cover in landscape ecology, with 25% of the articles reviewed using a binary classification scheme and 68% using a multi-class classification scheme (Table 1). However, many alternative methods are available to represent landscapes, such as point based and continuous field data and fuzzy sets (Gustafson 1998;Robinson 2007). This review found that these alternative methods were rarely used.…”
Section: Classification Scheme Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that discrete classification schemes were the dominant models used to represent land cover in landscape ecology, with 25% of the articles reviewed using a binary classification scheme and 68% using a multi-class classification scheme (Table 1). However, many alternative methods are available to represent landscapes, such as point based and continuous field data and fuzzy sets (Gustafson 1998;Robinson 2007). This review found that these alternative methods were rarely used.…”
Section: Classification Scheme Uncertaintymentioning
confidence: 99%
“…Already existing techniques for addressing spatial uncertainty are found more widely in the remote sensing and spatial science community. An example of this is the use of fuzzy classification schemes that are not patch based (Robinson 2007). In most cases though, these solutions tend to address a single form of spatial uncertainty and are often tailored to a given ecological model.…”
Section: Solutions To Spatial Uncertaintymentioning
confidence: 99%
“…The methods have found applications in other geosimulation domains too, in particular in hydrological modelling (Hemer 2006, Leyk et al 2005, Leyk et al 2004, Pappenberger et al 2006, Wealands et al 2005, Zappa et al 2008 and meteorological modelling (Ebert 2008, Cloke & Pappenberger 2008) and integrated assessment / ecological modelling (Nasiri & Huang 2008, van Delden et al 2007. Loonen et al 2006, Robinson 2007, Metzger et al 2005a. Many ecological models concern the spatial distribution of species.…”
Section: Current Applications and Further Developmentsmentioning
confidence: 99%